Bank merger premium : analysis and evidence - Beatty, Randolph P.; Santomero, Anthony M.; Smirlock, Michael L. (New York : Salomon brothers center, 1987)
This monograph describe the alternative techniques that can be used to structure bank mergers. The book empirically analyze the determinants of merger premium.
Includes bibliographical references p.35-36
ahz 12/03/2019
Loans
Keywords: Bank mergers